2006
DOI: 10.1159/000093119
|View full text |Cite
|
Sign up to set email alerts
|

Hair Follicles – A Long-Term Reservoir for Drug Delivery

Abstract: Nanoparticles represent an important drug carrier system. Recently, we have reported on the penetration and storage behavior of particular and non-particular substances revealing the superiority of particular substances in the range of 300–400 nm. In this regard, it was assumed that the rigid hair shaft acts as a geared pump, moving the particles deeper into the hair follicle. In the present investigation, the storage reservoir capacity of the stratum corneum and the hair follicle infundibulum and canal are co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
122
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 214 publications
(128 citation statements)
references
References 35 publications
3
122
0
3
Order By: Relevance
“…These applications cause general skin exposure, posing the potential risk of percutaneous absorption and ROS-mediated skin aging [43][44][45][46][47][48]. Skin is the body's first line of defense from the outside world.…”
Section: Skinmentioning
confidence: 99%
See 1 more Smart Citation
“…These applications cause general skin exposure, posing the potential risk of percutaneous absorption and ROS-mediated skin aging [43][44][45][46][47][48]. Skin is the body's first line of defense from the outside world.…”
Section: Skinmentioning
confidence: 99%
“…4), which facilitates transdermal drug delivery [49] but also provides a possible route for NP entry and a long-term NP reservoir. Although only 1% of applied TNPs were found in the orifices of hair follicles, these deposits were much harder to remove than those on the skin surface [45][46][47][48]. The stratum corneum (the upper layer of epidermis) shields against percutaneous penetration by most extraneous substances [50], but TNPs were shown to penetrate the stratum corneum and the stratum granulosum in pigs [44].…”
Section: Skinmentioning
confidence: 99%
“…These carriers can transport different types of drugs, including macromolecules, high lipophilic or hydrophilic drugs, favoring their penetration in the HF infundibulum. Whereas solutes are normally washed out, particulate materials can accumulate in the infundibulum and be retained there for days [10]. Depending on particle characteristics like size, surface functionalization and flexibility/deformability, different penetration depths and drug depot effects can be achieved.…”
Section: How To Improve Transfollicular Drug Delivery?mentioning
confidence: 99%
“…Recently, it was demonstrated that particles in general [4][5][6][7][8][9] and especially at a size between 300 and 600 nm penetrate very efficiently and deeper into the hair follicles than non-particulate substances [4,10]. Likewise, the storage time was found to be increased by up to 10 days, in the case of the particulate substances, which is significantly longer than 4 days, as observed for the non-particulate substances [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, in vitro, the movement of the hair has to be simulated by a massage appliance [11], under in vivo conditions, whereby a continuous movement of the hairs proceeds, pushing the particles efficiently and deeply into the hair follicles, if their size corresponds to the thickness of the keratin cells. Patzelt et al [14] revealed that, depending on the size of the nanoparticles, different depths and thereby different target structures within the hair follicle can be reached.…”
Section: Introductionmentioning
confidence: 99%